Displaced scapular body fracture treated with operative closed reduction - Michael Ghassibi; Dhanunjay Sarma Boyalakuntla; Sheryl Handler-Matasar (Elsevier, 2019)
Case: A majority of the pediatric scapula fractures sustained are scapular body fractures. There is a lack of literature concerning pediatric scapular body fractures and its management. We report the case of a scapular body fracture with significant angulation, our intraoperative closed reduction axillary fold approach under anesthesia, and the functional and radiologic outcomes post operatively. At 3 month and 2 year follow up, the patient was able to resume normal activities. Imaging demonstrated a completely healed, well aligned scapular body. Conclusions: We suggest closed reduction as an option in significantly angulated isolated scapular body fractures. Keywords: Case report, Scapula, Pediatric, Closed reduction, Scapular body fracture